Analysis of wearing masks compliance during the COVID-19 pandemic based on the Health Belief Model - Wijaya, Dhandi; Misnaniarti, Misnaniarti; Sitorus, Rico Januar (Public Health of Indonesia, 2021)
Background: Maintaining physical distance, washing hands, and wearing masks during the COVID-19 pandemic are very important in preventing the spread of the virus. However, although the use of facemasks is relatively easy to do, its compliance is considered low.Objective: This study aimed to analyze compliance in wearing masks during the COVID-19 pandemic.Methods: This cross-sectional study was conducted on 400 residents in Palembang, Indonesia, selected using simple random sampling from August to September 2021. Data were collected using online questionnaires and analyzed using descriptive statistics, Chi-square, and multivariate using logistic regression.Results: The findings revealed that sex, education, and employment status were significant relationships to compliance to wearing masks (p<0.05), but age and family income were not significantly related (p>0.05). Multivariate analysis showed only perceived severity and cues to action had a significant relationship with compliance to wearing masks after it was controlled by the sex variable (p<0.05), with PR of 0.558 (95% CI 0.331-0.941) and 0.410 (95% CI 0.242-0.696), consecutively.Conclusion: Perceived severity and cues to action are factors that influence compliance to wearing masks. Therefore, these two factors should be considered by public health practitioners as well as the government to increase the compliance wearing masks.